Synthesis of Mono‐ and Dihydroxylated Amino Acids with New α‐Ketoglutarate‐Dependent Dioxygenases: Biocatalytic Oxidation of CH Bonds. Issue 10 (11th September 2014) - Baud, Damien; Saaidi, Pierre‐Loïc; Monfleur, Adam; Harari, Marine; Cuccaro, Julien; Fossey, Aurélie; Besnard, Marielle; Debard, Adrien; Mariage, Aline; Pellouin, Virginie; Petit, Jean‐Louis; Salanoubat, Marcel; et al.
Abstract Iron(II)/α‐ketoacid‐dependent oxygenases (αKAOs) are enzymes that mainly catalyse hydroxylation reaction. By using a genomic approach combining sequence comparison and protein‐domain sharing, a set of 131 αKAO enzymes was prepared. The screening of various substrates revealed five new αKAOs. Four αKAOs were found to be active towards L‐lysine, L‐ornithine and L‐arginine with total regio‐ and stereoselectivities and yielding the corresponding 3‐ or 4‐hydroxyamino acids. The enzymatic cascade reaction with two stereoselective regiodivergent αKAOs enabled the synthesis of 3, 4‐dihydroxy‐L‐lysine.